Brand image perception and its influence on purchase decision: Celcom (M) Bhd / Sabariah Sidek - Sidek, Sabariah (2009)
Purchase decision is basically come through by customers and consumers perception that those already use the services and product which have in market. Sometimes, the changes of image by one company can make the loyal and new customers confuse. This study helps us extend our understanding of the relationship between purchase decision, perception and image. The objective of this paper is firstly to determine the perception of customers towards brand image on CELCOM (M) BHD. Secondly, to identify the strongest factor of the brand image. Thirdly, to examine the relationship selected respondent’s profile and purchase decision. Lastly is to recommendation to CELCOM management on how to improve their brand image to increase purchase from customers. The factors of brand image perception that contribute to the purchase decision are the network coverage, product offering, and the value and customer service. The objective of this research is a also to identify the factor of image and perception that are positively related to purchase decision on CELCOM (M) BHD.